Evaluation of oxidative stress and proinflammatory cytokines in gestational diabetes mellitus and their correlation with pregnancy outcome - K A Sudharshana Murthy; Ambarisha Bhandiwada; Shivani L Chandan; Surakshith L Gowda; G Sindhusree (Indian Journal of Endocrinology and Metabolism, 2018)
Background: Prevalence of Gestational Diabetes Mellitus in India is increasing. In addition to performing physiological role in fetoplacental unit during pregnancy, cytokines also play pathophysiological role if expressed in abnormal amounts or sites. Objective: To estimate Proinflammatory Cytokines TNF-α, IL-6, IL-8 and anti-oxidants Glutathione Peroxidase (GTX), Superoxide dismutase (SOD), uric acid and Bilirubin levels in GDM and correlate with pregnancy outcome. Results: Pregnant women were screened for GDM using Diabetes In Pregnancy Study group, India criteria. The subjects with elevated glucose were grouped into cases (n = 30) and with normal values were taken as controls (n = 30). Mean Uric acid in cases was 4.53 ± 1.2 mg% whereas in controls 3.13 ± 0.58 mg%, mean TNF-α among cases was 6.06 ± 3.6 pg/ml and controls 2.81 ± 1.03 pg/ml. Antioxidants SOD and GTX were markedly decreased with mean value of 4979.21 ± 1006.3 and 13.68 ± 1.5 in cases and 9625.10 ± 1074.1 and 15.86 ± 1.2 in controls. Cytokines IL-6 (2.96 + 1.37 vs 2.88 + 1.21) and IL-8 (7.76 + 3.86 vs 2.60 + 1.45) were increased in subjects with GDM. Those with GDM developed preeclampsia (5%), Preterm labour (2%) and Polyhydromnios (5%). Foetal complications Macrosomia (13.3%) and intra uterine death (3.3%) were observed in GDM mothers. The proinflammatory cytokine levels except IL-6 were significantly increased and antioxidant markers were significantly reduced in GDM group with maternal and foetal complications. Conclusion: GDM worsens the oxidative stress and weakens anti-oxidant state. Uric acid, TNF-α and IL-8 were higher with foeto-maternal complications in GDM. Serum bilirubin, GTX and SOD is significantly lower in foeto-maternal complications. TNF-α significantly associated with preeclampsia in GDM mothers.